EXTERNAL FINANCIAL FLOWS AND ALL SHARE INDEX IN THE NIGERIAN CAPITAL MARKET: VECM FRAMEWORK - OLAWALE, FOLORUNSHO THOMAS; ADEGBEMI, BABATUNDE ONAKOYA; BIOLA, PHILLIP (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2023)
In many economies, the capital markets play a vital role as one of the most powerful drivers of economic growth and wealth creation. This research work aims to assess the dynamic effects of external financial flows on the All-Share Index of Nigerian capital market over the period 1981-2020. The study employed the VECM and regressors’ and ECT t-statistics causality approaches to establish the short, long and strong relationship. The study found that FPI, remittance from personal transfers, remittance from compensation of employees, TOP and ODA have positive impacts on ASI in the long run except for the FDI. The findings on ECT t-statistics causality relationship were mixed-revealing, the result shows that some variables were statistically significant in the short-run and also in the long-run, these joint statistically significance between the variables in the short-run and long-run implies strong causal relationship among the variables. This implies that external financial flows tend to generate unpredictable and a typical influences on long-term capital market development in Nigeria, although it gives little room for short-run development of the market. The study suggested that the policy measures aimed at directing long run capital inflows should not be the same as those aimed at changing the short run patterns of flow. Thus, policy makers must develop policy directions to suit the time horizon of capital flows in enhancing market value, price stability and liquidity.